SMEs navigating in complex environments - Grandinetti, Roberto; Pencarelli, Tonino (Piccola Impresa / Small Business, 2024)
Purpose: The aim of this editorial is to develop a reflection on how small and medium enterprises (SMEs) can face the complexity that increasingly characterizes the competitive environments in which they live. Findings: After defining environmental complexity, the editorial links it to the concept of ambidexterity, that is, the classic dichotomy between exploration and exploitation. In particular, the different forms of organizational ambidexterity are analyzed, emphasizing the solutions (of contextual ambidexterity) that are accessible to SMEs. Practical and Social Implications: The editorial suggests and discusses two strategies that are sustainable by SMEs dealing with environmental complexity: learning to manage the (contextual) ambidexterity paradox, and SMEs’ growth through acquisitions and networking. Originality of the Study: SMEs and their strategic behavior are originally analyzed through the two complementary approaches of organizational ambidexterity and organizational paradoxes.